The study of honokiol as a natural product-based antimicrobial agent and its potential interaction with FtsZ protein - Sun, Ning; Zhi, Ziling; Xiao, Ting; Deng, Xin; He, Tenghui; Dong, Wanyang; Feng, Shuyi; Chen, Sisi; Wong, Wing-Leung; Yuan, Wenchang (Frontiers in Microbiology, 2024)
Multidrug resistant bacteria have been a global health threat currently and frontline clinical treatments for these infections are very limited. To develop potent antibacterial agents with new bactericidal mechanisms is thus needed urgently to address this critical antibiotic resistance challenge. Natural products are a treasure of small molecules with high bioactive and low toxicity. In the present study, we demonstrated that a natural compound, honokiol, showed potent antibacterial activity against a number of Gram-positive bacteria including MRSA and VRE. Moreover, honokiol in combination with clinically used β-lactam antibiotics exhibits strong synergistic antimicrobial effects against drug-resistant S. aureus strains. Biochemical studies further reveal that honokiol may disrupt the GTPase activity, FtsZ polymerization, cell division. These biological impacts induced by honokiol may ultimately cause bacterial cell death. The in vivo antibacterial activity of honokiol against S. aureus infection was also verified with a biological model of G. mellonella larvae. The in vivo results support that honokiol is low toxic against the larvae and effectively increases the survival rate of the larvae infected with S. aureus. These findings demonstrate the potential of honokiol for further structural advancement as a new class of antibacterial agents with high potency against multidrug-resistant bacteria.